Основні аспекти формування світогляду майбутніх лікарів - Гиря, Олена Максимівна; Hyrya, O. M. (My University, 2014)
У статті відображені основні аспекти і проблеми формування світогляду майбутніх лікарів по підготовці з дисципліни “Педіатрія” на сучасному етапі. The article displays the main aspects and problems of formation of worldview in future doctors during the process of preparation on the discipline of Pediatrics at the present stage.
Main aspects of forming of worldview of future doctors